2007
DOI: 10.1002/adma.200600793
|View full text |Cite
|
Sign up to set email alerts
|

Chain‐Scission‐Induced Intercalation as a Facile Route to Polymer Nanocomposites

Abstract: Polymer/clay nanocomposites (NCs) prepared using melt intercalation must be properly formulated and processed to achieve intercalation or exfoliation. Organically modified layered silicates (OMLSs) are often used to permit polymer intercalation and thereby separate the silicate platelets. Prior modeling efforts [1] suggest that high-molecular-weight (HMW) polymers tend to yield immiscible NCs unlike their low-molecular-weight (LMW) analogs, which commonly result in exfoliated or intercalated NCs. Although form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In the materials category, polymer nanocomposites, hailed as a “radical alternative to conventional filled polymers or polymer blends”1 and “a revolutionary new class of materials that have demonstrated vastly improved properties compared to those of conventional composites”,2 are experiencing an unprecedented rapid development. Carbon nanofibers, carbon nanotubes, and layered silicates have been extensively studied and used as nanofillers to improve the mechanical, thermal, electrical, and gas barrier properties of various polymers 3–10. Recently, thanks to the development of effective chemical and thermal reduction methods of graphite oxide (GO), large scale preparation of graphene, the one‐atom‐thick sp 2 ‐carbon sheet material with overall mechanical properties and thermal and electrical conductivities surpassing or at least rivaling those of the best existing nanofillers (e.g., single‐wall carbon nanotubes), has become realistic 11–15.…”
Section: Introductionmentioning
confidence: 99%
“…In the materials category, polymer nanocomposites, hailed as a “radical alternative to conventional filled polymers or polymer blends”1 and “a revolutionary new class of materials that have demonstrated vastly improved properties compared to those of conventional composites”,2 are experiencing an unprecedented rapid development. Carbon nanofibers, carbon nanotubes, and layered silicates have been extensively studied and used as nanofillers to improve the mechanical, thermal, electrical, and gas barrier properties of various polymers 3–10. Recently, thanks to the development of effective chemical and thermal reduction methods of graphite oxide (GO), large scale preparation of graphene, the one‐atom‐thick sp 2 ‐carbon sheet material with overall mechanical properties and thermal and electrical conductivities surpassing or at least rivaling those of the best existing nanofillers (e.g., single‐wall carbon nanotubes), has become realistic 11–15.…”
Section: Introductionmentioning
confidence: 99%
“…[261] AIBN was introduced in organic-modified MMT, after which PS was intercalated from melt. Some increase in interplanar distance can be related with exothermal process of decomposition of the initiator and forming of free volume due to gas emission, which accelerates exfoliation [268]. Extrusion of a polymer with aggregated silicate (Fig.…”
Section: Nanocomposites Based On Non-polar Thermoplastics Produced Bymentioning
confidence: 99%
“…As to nonpolar polymer matrix, for example, polypropylene, the kinetics of changes in clay dispersion was relative slow, but, interestingly, after certain long waiting duration a gel‐like rheological character appeared in the logarithmical relation between storage modulus and annealing time 11, 12. Spontak and coworkers13 suggested that the phenomenon of self‐occurred intercalation/exfoliation under quiescent molten condition can be utilized as a facile route to attain well‐dispersed PCNs. However, in past literature, the rheological investigations about structural alteration of PSNs melt were almost implemented upon isothermal situation, whereas the variable temperature process was rarely concerned 14.…”
Section: Introductionmentioning
confidence: 99%